Fungicides selection for the control of the entomosporiosis in quince trees - Soares, José Manoel (Pesquisa Agropecuaria Brasileira, 1991)
The development of blight on leaves of quince trees (Cydonia vulgaris L.) treated four times with dodine, iprodione, triforine and methyl-thiophanate was observed during the 1988/1989 cycle, with intervals of at least 30 days between the phytosanitary treatments.